A conceptual understanding of criminality and integrity challenges in food supply chains. Issue 1 (3rd January 2017) - Fassam, Liam; Dani, Samir
Abstract : Purpose: Business, consumers and governmental organisations are harbouring a growing need to gain an appreciation of behaviours connected to food criminality. In order to acquire a cross-functional understanding of these thematic areas (crime and fraud) the mapping of existing research is needed. The paper aims to discuss these issues. Design/methodology/approach: This paper contributes to the process of knowledge understanding, by systematically reviewing literature to provide an analysis of the current body of business knowledge against the thematic criterion of "supply chain food crime" and "supply chain food fraud". The analysis derives themes from the literature and maps this across the eight pillars underpinning the UK Government paper on food supply chain resilience. Findings: A distinct gap lies with the eight pillars of food supply chain resilience, business interest into supply chain criminality and academic research into the field. There are noteworthy gaps when the literature is analysed to that of the UK Government report. Research limitations/implications: The limitation of the study was its focus on business-only journals; a plethora of literature resides in the science field (e.g. testing) that has not made its way to business text. Practical implications: Drawing inference between business research and the government report, clear identification and tangible research areas can be immediately exploited to align cross-functional thinking. Social implications: The gap of consumer is not as yet addressed in this field, this research contributes originally to this gap and the need to address the same for societal benefit. Originality/value: The paper concentrates on the metrics know to contribute to "food crime" and "food fraud" and deviating views of academic vs non-academic literature. In conclusion the paper identifies thematic areas for further research and presents a conceptual framework of food supply chain resilience.